Exercise-Induced Right Ventricular Outflow Tract Tachycardia in a Patient with Isolated Left Ventricular Noncompaction. (26th May 2011) - Güvenç, Tolga Sinan; İlhan, Erkan and Alper, Ahmet Taha and Eren, Mehmet
Abstract : Isolated left ventricular noncompaction is a hereditary cardiomyopathy in which a variety of supraventricular and ventricular arrhythmias could be observed. We report a patient with exercise-induced ventricular tachycardia with left bundle branch block morphology that had characteristics of an idiopathic ventricular tachycardia who was subsequently diagnosed as left ventricular noncompaction. Successful remission of arrhythmia was ensured after the introduction of oral beta-blocker therapy.